PENGARUH PEMBERIAN PENGUATAN TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPS PADA SISWA SEKOLAH DASAR DI KABUPATEN PESISIR BARAT - Sriwardani, Fitri; Mazdayani, Mazdayani (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2020)
The purpose of this study was to determine whether there was an effect of strengthening the learning outcomes of fourth-grade elementary school students in social studies subjects. The method used in this research is quantitative pre-experimental design in the form of one group pretest-posttest design. This study is a population study with a sampling technique using all members of the population as the research sample. The sample of this study was 20 grade IVA students with the research location of SD Negeri 46 Krui, Pesisir Barat. The results showed that the provision of reinforcement had an effect on student learning outcomes in the social studies subject for class IVA even semester of the 2019/2020 academic year. The results of this study used a different method from the research conducted by Rohani (2019), the method used was a descriptive method with the form of research being a relationship study. The results of this study indicate that there is an effect of strengthening by the teacher on student learning outcomes in class VII PKN learning at SMP Negeri 4 Rasau Jaya, Kubu Raya Regency.